Assessment of lipid profile and acute phase protein in Mycobacterium avium subspecies paratuberculosis infected and healthy goats - SHARMA, SHALINI; SINGH, SHOOR VIR; GAUTAM, AJAY KUMAR; MISHRA, SUMIT RANJAN; GUPTA, SAURABH; CHAUBEY, KUNDAN KUMAR; SANGWAN, NIRMAL (The Indian Journal of Animal Sciences, 2020)
Present study is based on 24 goats that were located in goat herds endemically infected with Mycobacterium avium subspecies paratuberculosis (MAP) infection. Objective of the study was to access the variations in the lipid profile and acute phase proteins in the serum samples driven from non-infected (negative and physically healthy) and infected (positive and physically weak) goats with MAP infection, cause of incurable Johne’s disease (JD) in domestic livestock. Infected goats had significantly higher cholesterol and albumin levels and significantly ‘reduced level’ of high density lipoprotein (HDL) and ‘reduced level’ of the density of lipoproteins (LDL) in comparison to non-infected goats. Lipid profile and acute phase proteins could be further explored for their significance in pathogenesis and diagnosis of JD in domestic livestock including goats.